Electron microscopy and single molecule averaging of subunit-deficient F1-ATPases from Escherichia coli and spinach chloroplasts. - Akey, C W (1983)
The morphology of F1-ATPases lacking one or more small subunits has been investigated by minimal-beam electron microscopy of close-packed monolayers of molecules. Computer-based rotational analyses of single molecules were performed on reconstituted 3-subunit F1-ATPase (-delta epsilon) from Escherichia coli and both 3-subunit (-delta epsilon) and 4-subunit (-delta) F1-ATPase from chloroplasts. Optical diffraction measurements of close-packed arrays revealed maximal dimensions of 122 +/- 4 A and 129 +/- 9 A for 3-subunit ECF1 and 4-subunit CF1, respectively. Molecules which displayed either hollow or solid hexagonal morphologies were observed in all preparations. Averaged reconstructions were obtained from molecules with hollow morphologies in 3-subunit preparations and demonstrated strong hexagonal symmetry in projection with a central, stain-filled cavity. The average reconstruction obtained from molecules with the solid morphology in 4-subunit CF1 preparations, was also strongly hexagonal with six peripheral units ringed about a central subunit. Differences between hollow and solid morphologies cannot be attributed solely to the presence or absence of the delta and epsilon subunits; therefore, the two image types may represent staining variants of a common structure. Overall, the reconstructions are consistent with an alpha 3 beta 3 gamma stoichiometry for the coupling factors from both E. coli and chloroplasts.